Desktop Based Furniture Sales Information System (Case Study: Faiza Houseware & Furniture Store) - Sembiring, Binaria Br; Marbun, Nasib (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
This study aims to build a desktop-based furniture sales information system at Faiza Houseware & Furniture Store. Toko Faiza Houseware & Furniture is one of the stores engaged in the sale of furniture products such as tables, benches, beds, and kitchen sets. Until now, Faiza Houseware & Furniture Store has not utilized information system technology to support its sales data processing. Toko Faiza Houseware & Furniture still utilizes ledgers to record furniture sales data reports that are made every day. So that data corruption and even data loss often occurs. The data collection techniques used are observation, interviews, and literature studies. The programming language that the author uses to build a desktop-based furniture sales information system that will be implemented at Toko Faiza Houseware & Furniture is Visual Basic .Net. Visual Basic Net is an object-oriented programming language that allows users to create applications with visual techniques. The tool used by the author as a data storage in the desktop-based furniture sales information system built is Microsoft Access. Data reports processed in the desktop-based furniture sales information system can be displayed and printed through Crystal Report. The results showed that the desktop-based furniture sales information system built in this study can improve operational performance and customer service by speeding up and simplifying the furniture sales process at Toko Faiza Houseware & Furniture.